Are the current difficulty scores for laparoscopic liver surgery telling the whole story? An international survey and recommendations for the future. Issue 3 (March 2018) - ,; Abu Hilal, M.; Aldrighetti, L.; Al Saati, H.; Alseidi, A.; Aroori, S.; Belli, G.; Besselink, M.; Edwin, B.; D'Hondt, M.; Dagher, I.; Dejong, C.; et al.
Abstract: Background: Recent studies have suggested that the difficulty of laparoscopic liver resections are related to both patient and tumour factors, however the available difficulty scoring systems only incorporate tumour factors. The aim of this study was to assess the opinion of laparoscopic liver surgeons regarding the factors that affect the perceived difficulty of laparoscopic liver resections. Method: Using a Visual Analogue Scale an international survey of laparoscopic liver surgeons was undertaken to assess the perceived difficulty of 26 factors previously demonstrated to affect the difficulty of a laparoscopic liver resection. Results: 80 surgeons with a combined experience of over 7000 laparoscopic liver resections responded to the survey. The difficulty of laparoscopic liver surgery was suggested to be increased by a BMI > 35 by 89% of respondents; neo-adjuvant chemotherapy by 79%; repeated liver resection by 99% and concurrent procedures by 59% however these factors have not been included in the previous difficulty scoring systems. Conclusion: The results suggests that the difficulty of laparoscopic liver surgery is not fully assessed by the available difficulty scoring systems and prompts the development of a new difficulty score that incorporates all factors believed to increase difficulty.